Analysis of nacl-mannitol hydration on renal function of head and neck cancer patients receiving high-dose cisplatin chemotherapy combination - Desiani, Ekanita; Suharjono, Suharjono; Yulistiani, Yulistiani; Susilo, Dwi Hari (Folia Medica Indonesiana, 2017)
Cisplatin is one of platinum cytostatic drug for the medication of solid cancers, one of which is head and neck cancer. Adverse event that resulted during drug treatment was acute or chronic nephrotoxicity. Cisplatin concentration in proximal tubular epithelial cells is about 5 times the serum concentration. Platinum exposure on renal tubular cells bonding covalent complex which stimulate production of inflammatory factors that lead to apoptosis and necrosis cell. Cisplatin nephrotoxicity can be prevented by aggressive hydration or alternate method of administration. The aim of this study was to analyze the effectiveness of NaCl-Mannitol hydration on renal function of head and neck cancer patients receiving cisplatin 100 mg/m2 chemotherapy combination with 5FU or paclitaxel. This was a cohort, prospective, and observational study to analyze renal function of head and neck cancer patients receiving cisplatin 100 mg/m2 chemotherapy combination with 5FU or paclitaxel. Inclusion criteria were BUN 7-18 mg/dl and serum creatinine < 2 mg/dl of any cycle. All patients received infuse NaCl-Mannitol hydration with term that provided in Surgeon Departement of Dr. Soetomo General Hospital. Data obtained were BUN, SCr, and eClCr Cockroft-Gault, each was measured pre- and post-hydration. In cisplatin and 5FU chemotherapy combination value BUN pre-hydration (11,99 + 4,62) mg/dl, value BUN post-hydration (12,14 + 4,74) mg/dl and value serum creatinine pre-hydration (0,97 + 0,34) mg/dl, value serum creatinine post-hydration (1,02 + 0,37) mg/dl. Meanwhile to the combination of cisplatin and paclitaxel chemotherapy, value BUN pre-hydration (10,19 + 2,58) mg/dl, value of BUN post-hydration (10,43 + 2,31) mg/dl and value of serum creatinine post- hydration (0,98 + 0,26) mg/dl. In conclusion, NaCl-Mannitol hydration administration is adequate which is shown by BUN and serum creatinine in pre- and post-hydration data within normal limits.